Shark vs. train - Barton, Chris; Lichtenheld, Tom (New York, NY : Little, Brown and Co., 2010)
A shark and a train compete in a series of contests on a seesaw, in hot air balloons, bowling, shooting baskets, playing hide-and-seek, and more.
A Junior Library Guild selection
Keywords: Competition (Psychology) -- Juvenile fiction; Sharks -- Juvenile fiction; Railroad trains -- Juvenile fiction; Competition (Psychology) -- Fiction; Sharks -- Fiction; Railroad trains -- Fiction; Picture books